Towards a poetics of a contemporary Broadway sound: orchestration techniques in Alan Menken’s Disney musicals and their application to a contemporary south African musical - Bezuidenhout, Stephanus Abraham (Stellenbosch : Stellenbosch University, 2025)
Bezuidenhout, Stephanus Abraham. 2024. Towards a poetics of a contemporary Broadway sound: orchestration techniques in Alan Menken’s Disney musicals and their application to a contemporary south African musical. Unpublished doctoral dissertation. Stellenbosch : Stellenbosch University [online]. Available: https://scholar.sun.ac.za/handle/10019.1/131577